ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) INA GELEKAT KABUPATEN FLORES TIMUR - Lewuk, Yosefinа Letek; Londа, Yulitа; Thalib, Sabra B. Wahab (Program Studi Akuntansi Universitas Flores, 2024)
The aim to be achieved in this research is to determine the financial performance of the Ina Gelekat Regional Drinking Water Company, East Flores Regency for 3 (three) years, namely 2019-2021, viewed from the financial aspect based on Decree of the Minister of Home Affairs Number 47 of 1999. The data obtained taken in the form of financial report data for PDAM Ina Gelekat, East Flores Regency from 2019-2021. The type of research of research used is quantitative descriptive research. This study uses primary data, namely interviews and secondary data, namely financial report documents. The data analysis method in this research is quantitative descriptive analysis, with a financial ratio approach with the basic data needed for analysis in the form of a balance sheet and profit and lost report for 2019-2021, guided by Decree of the Minister of Home Affairs Number 27 of 1999 concerning Guidelines for Regional Company Performance Assessment Drinking Water to assess the financial aspect. The results of this research show that the financial performance value obtained by PDAM Ina Gelekat, East Flores Regency in 2019 was 21, in 2020 it was 24,75, and in 2021 it was 28,5. Overall, the financial performance of PDAM Ina Gelekat, East Flores Regency in 2019-2021 is included in the not good category according to the determined level of success. Therefore, the author suggests that the East Flores Regency Government, especially PDAM Ina Gelekat, East Flores Regency, further increase the company's income by increasing water sales. The company also minimizes the use of operational cost by disciplining unnecessary cost. Thus it can improve several indicators on the financial aspect.